Tuning Molecular Self‐Assembly Toward Intriguing Nanomaterial Architectures. Issue 28 (24th May 2013) - Lee, Ju Young; Hong, Byung Hee; Kim, Dong Young; Mason, Daniel R.; Lee, Jung Woo; Chun, Young; Kim, Kwang S.
<x xml:space="preserve">Abstract</x> Taking shape nicely: The shaping of electro‐ and photochemically active calix[4]hydroquinone (CHQ) into nanoplates, ‐polygons and ‐tubes and their dynamic conversion into nanospheres and ‐hemispheres is demonstrated (see figure). CHQ nanostructures can be used to produce nanoshells and ‐cups with diverse shapes and sizes for a range of noble‐metal‐ coated highly tunable plasmonic materials, generated without additional reducing agent.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>